Array-based MLPA to detect recurrent copy number variations in patients with idiopathic mental retardation - Rooms, Liesbeth; Vandeweyer, Geert; Reyniers, Edwin; van Mol, Kurt; de Canck, Ilse; Van der Aa, Nathalie; Rossau, Rudi; Kooy, R. Frank (American journal of medical genetics. Part A, 2011)
Microdeletions, either subtelomeric or interstitial, are responsible for the mental handicap in approximately 10–20% of all patients. Currently, Multiplex Ligation‐dependent Probe Amplification (MLPA) is widely used to detect these small aberrations in a routine fashion. Although cost‐effective, the throughput is low and the degree of multiplexing is limited to maximally 40–50 probes. Therefore, we developed an array‐based MLPA method, with probes identified by unique tag sequences, allowing the simultaneous analysis of 180 probes in a single experiment thereby covering all known mental retardation loci with at least two probes. We screened 120 patients with idiopathic mental retardation. In this group we detected 6 aberrations giving a detection rate of 5%, consistent with similar studies. In addition we tested 293 patients with mental retardation who were negative for fragile X syndrome and commercially available subtelomeric MLPA. We found seven causative rearrangements in this group (detection rate of 2.4%) thereby illustrating the value of including probes for interstitial microdeletion syndromes and additional probes in the telomeric regions in targeted screening sets for mental retardation. Array‐based MLPA may thus be a good candidate to develop probe sets that rapidly detect copy number changes of disease associated loci in the human genome. This method may become a valuable tool in a routine diagnostic setting as it is a fast, user‐friendly and relatively low‐cost technique providing straightforward results requiring only 125 ng of genomic DNA. © 2011 Wiley‐Liss, Inc.